2017
DOI: 10.1038/s41598-017-12428-x
|View full text |Cite
|
Sign up to set email alerts
|

Stability and optical properties of plutonium monoxide from first-principle calculation

Abstract: The resolution of questions about the existence of condensed plutonium monoxide (PuO) has long been hindered by lack of thermochemical data. Here we perform first-principles calculation to investigate the reaction Pu2O3 + Pu → 3 PuO and find that PuO is thermodynamically unstable under ambient pressure. We also find that pressure could stabilize PuO by strengthening the hybridization between Pu-5f/6d and O-2p states. Moreover, the dynamical stability of NaCl-type PuO is verified by the phonon calculation. Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…This holds for the some nonmetallic elements such as H and N with weak oxidizability judged from their borderline compounds PuH 3 and PuN . Pu 2+ had not been detected in the binary compounds for a long time; even the unstable PuH 2 and PuO (exactly, stabilized by C, i.e., PuC x O 1– x ) were determined to be trivalent-like Pu ions with a surplus 5f conduction electron, resulting in the metallic states of PuH 2 and PuO, whereas PuH 3 and Pu 2 O 3 are semiconducting states. Clearly, the valence or OS can be readily changed by more electronegative elements. With the transition of Pu 2 O 3 → PuO 2 → PuO 2+ x , , Pu 5f electrons become more delocalized with the typical feature of fewer 5f states below Fermi energy ( E F ) and are expected to be further delocalized in the crystallographically identified Pu–O–F ternary solid compounds, such as PuO 2 F, PuO 2 F 2 , and PuOF 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This holds for the some nonmetallic elements such as H and N with weak oxidizability judged from their borderline compounds PuH 3 and PuN . Pu 2+ had not been detected in the binary compounds for a long time; even the unstable PuH 2 and PuO (exactly, stabilized by C, i.e., PuC x O 1– x ) were determined to be trivalent-like Pu ions with a surplus 5f conduction electron, resulting in the metallic states of PuH 2 and PuO, whereas PuH 3 and Pu 2 O 3 are semiconducting states. Clearly, the valence or OS can be readily changed by more electronegative elements. With the transition of Pu 2 O 3 → PuO 2 → PuO 2+ x , , Pu 5f electrons become more delocalized with the typical feature of fewer 5f states below Fermi energy ( E F ) and are expected to be further delocalized in the crystallographically identified Pu–O–F ternary solid compounds, such as PuO 2 F, PuO 2 F 2 , and PuOF 4 .…”
Section: Introductionmentioning
confidence: 99%
“…to illustrate that PuO is thermodynamically unstable at ambient pressure and will probably decompose into Pu 2 O 3 and Pu. 15 A number of researchers have suggested that PuO could be stabilized by carbon impurity. [11][12][13]18 The further question is about the thermodynamical stability of carbonsubstituted PuO, i.e., PuO x C y , with respect to Pu 2 O 3 and Pu.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In other words, limited oxygen vacancies weaken the strength of the Ce–O bonds; however, they cannot fundamentally alter the electron-match character until the borderline Ce 2 O 3 . Further removing oxygen from Ce 2 O 3 is expected to result in a metallic state, similar to the analogue Pu 2 O 3 and other low valence metal oxides. , …”
Section: Results and Discussionmentioning
confidence: 95%
“…The DOS profiles of stoichiometric oxides or impurity-doped oxides allow us to find whether or not the in-gap states resultant from localized electrons are formed. 42 43,44 The changes in the band gap and energy profile are bound to be reflected in the electronic and optical response, which establishes the basic principle for tailoring ceria. The changes are particularly remarkable for the ternary and quaternary Ce oxides, as shown in Figure 4.…”
Section: Computational Approachmentioning
confidence: 99%